Propofol and arrhythmias: two sides of the coin - Liu Qiang; Kong Ai-ling; Chen Rong; Qian Cheng; Liu Shao-wen; Sun Bao-gui; Wang Le-xin; Song Long-sheng; Hong Jiang (Acta Pharmacologica Sinica, 2016)
The hypnotic agent propofol is effective for the induction and maintenance of anesthesia. However, recent studies have shown that propofol administration is related to arrhythmias. Propofol displays both pro- and anti-arrhythmic effects in a concentration-dependent manner. Data indicate that propofol can convert supraventricular tachycardia and ventricular tachycardia and may inhibit the conduction system of the heart. The mechanism of the cardiac effects remains poorly defined and may involve ion channels, the autonomic nervous system and cardiac gap junctions. Specifically, sodium, calcium and potassium currents in cardiac cells are suppressed by clinically relevant concentrations of propofol. Propofol shortens the action potential duration (APD) but lessens the ischemia-induced decrease in the APD. Furthermore, propofol suppresses both sympathetic and parasympathetic tone and preserves gap junctions during ischemia. All of these effects cumulatively contribute to the antiarrhythmic and proarrhythmic properties of propofol.